The installation and support of internationally distributed equipment for people with dementia. - Adlam, T. (IEEE Transactions on information technology in biomedicine)
This paper describes the evaluation and support of assistive technology designed to increase the independence of people with dementia. Devices were evaluated by people with dementia in their own homes. Working with and supporting people with dementia requires relational skills not normally needed by installers and technical supporters.